Screening of 30 acidic and neutral pharmaceuticals in whole blood by fully automated SPE and UPLC‐TOF‐MSE. Issue 4 (16th January 2013) - Dalsgaard, Petur Weihe; Rode, Andrej Jaroslav; Pedersen, Anders Just; Rasmussen, Brian Schou; Windberg, Charlotte Norup; Linnet, Kristian
<x xml:space="preserve">Abstract</x> A fully automated solid‐phase extraction (SPE) and ultra‐performance liquid chromatography time‐of‐flight mass spectrometry (UPLC‐TOF‐MSE) method for screening of 30 acidic and neutral pharmaceuticals in whole blood was developed and validated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>